Biblical Citations as a Stylistic Standard in Johnson’s and Webster’s Dictionaries - Cynthia L. Hallen; Tracy B. Spackman (Lexis: Journal in English Lexicology)
Noah Webster’s primary source for the first edition of the 1828 American Dictionary of the English Language (ADEL) was Samuel Johnson’s 1799 eighth edition of the Dictionary of the English Language (DEL). Scholars have made much of the debt that Webster owes to Johnson for entries in the 1828 ADEL. Stylistic analyses have typically focused on the definitions included in the two dictionaries. Far less attention has been paid to the illustrative quotations employed by both authors to exemplify usage. This article focuses on Biblical citations in the letter S used by both Johnson and Webster as examples of usage. All citations (both secular and Biblical) under the letter S were examined to determine the relative importance of the Bible to the style and content of the dictionaries. Results indicate that though Johnson included more Biblical citations than Webster did, Biblical citations made up a larger proportion of Webster’s total citations than they did for Johnson.In addition to ascertaining frequency of Biblical citations, all Biblical citations shared by both dictionaries were also identified. Results of this analysis confirmed Webster’s debt to Johnson, as a great number of Webster’s Biblical citations may be found in Johnson’s dictionary. A study of the religious convictions of Johnson and Webster is integral to understanding both authors’ motivations in constructing their dictionaries. Though both were pious men, Johnson’s focus on the Bible was as a great literary work, whereas Webster’s focus on the Bible was as a tool for the religious and moral betterment of his readers.